Dynamic hierarchical ligand anisotropy for competing macrophage regulation in vivo - Kanghyeon Kim; Sunhong Min; Ramar Thangam; Kyong-Ryol Tag; Hyun-Jeong Lee; Jeongyun Heo; Hwapyung Jung; Thet Thet Swe; Iman Zare; Guosheng Song; Alireza Hassani Najafabadi; Junmin Lee; et al. (Bioactive Materials)
Diverse connective tissues exhibit hierarchical anisotropic structures that intricately regulate homeostasis and tissue functions for dynamic immune response modulation. In this study, remotely manipulable hierarchical nanostructures are tailored to exhibit multi-scale ligand anisotropy. Hierarchical nanostructure construction involves coupling liganded nanoscale isotropic/anisotropic Au (comparable to few integrin molecules-scale) to the surface of microscale isotropic/anisotropic magnetic Fe3O4 (comparable to integrin cluster-scale) and then elastically tethering them to a substrate. Systematic independent tailoring of nanoscale or microscale ligand isotropy versus anisotropy in four different hierarchical nanostructures with constant liganded surface area demonstrates similar levels of integrin molecule bridging and macrophage adhesion on the nanoscale ligand isotropy versus anisotropy. Conversely, the levels of integrin cluster bridging across hierarchical nanostructures and macrophage adhesion are significantly promoted by microscale ligand anisotropy compared with microscale ligand isotropy. Furthermore, microscale ligand anisotropy dominantly activates the host macrophage adhesion and pro-regenerative M2 polarization in vivo over the nanoscale ligand anisotropy, which can be cyclically reversed by substrate-proximate versus substrate-distant magnetic manipulation. This unprecedented scale-specific regulation of cells can be diversified by unlimited tuning of the scale, anisotropy, dimension, shape, and magnetism of hierarchical structures to decipher scale-specific dynamic cell-material interactions to advance immunoengineering strategies.